Spanish Exhibition (leaflet)
018b-0036-001 SPANISH EXHIBITION In support of anti-fascist Spain—see in posters, photographs and pictures the background and causes of the war, Franco's allies, the International Brigade, care of the refugees, the work of reconstruction in schools, hospitals and factories. 36 LUDGATE HILL, E.C.4 20th Feb. to 20th March AFTERWARDS THROUGHOUT THE COUNTRY 11 am to 9pm ADMISSION FREE Proceeds for Relief work in Spain Published, by Spanish Exhibition Committee, 82 Cliffords Inn, E.C 4;. and printed by the Farleigh Press (T.U throughout), 17-29, Cayton Street, E.C.1. 292/946/18b/36